Fatigue strength evaluation of thin plate butt joints considering initial deformation. (August 2019) - Shen, Wei; Qiu, Yu; Li, Chunmei; Hu, Yaoyu; Li, Mengzhen
Highlights: The stress amplification factor considering the initial deformation effect of thin plates is derived. Nonlinear finite element calculation and fatigue test results are used to verify the feasibility of the modified formula. The modified formula can accurately reflect the stress concentration effect of thin plates butt joints. Abstract: In addition to dislocation and welding angle deformation during the processing of welded joints of thin plates, additional curvature deformation will occur in the thin plates, which is defined as the initial deformation of the plates. Due to the existence of dislocation and angular deformation, additional secondary bending moment effect will appear in the welded structure, which will affect the stress concentration at the weld toe. Therefore, DNV and IIW specifications recommend the stress amplification factor formula caused by welding imperfections. However, the current evaluation formula is mostly applicable to the stress concentration correction of thick plate welded structures, which does not consider the additional initial deformation effect caused by thin plate welding. Therefore, on the basis of the revised formula for thick plates, the stress amplification factor considering the initial deformation effect of thin plates is derived in this paper, and the calculation results are compared with those in traditional codes. Nonlinear finite element calculation results and fatigue test results are used to verify the feasibility and validity of the formula. The results show that, when considering the initial deformation of welding plates, the traditional code formula has a large error, and the revised calculation results are in good agreement with the finite element calculation results, which can accurately reflect the stress concentration effect at the welding toe of the thin plates butt joints.